2D Programmable Photodetectors Based on WSe2/h‐BN/Graphene Heterojunctions - Zhihao Wang; Jialing Jian; Zhengjin Weng; Qianqian Wu; Jian Li; Xingyu Zhou; Wei Kong; Xiang Xu; Liangliang Lin; Xiaofeng Gu; Peng Xiao; Haiyan Nan; et al. (Advanced Science)
Abstract Programmable photovoltaic photodetectors based on 2D materials can modulate optical and electronic signals in parallel, making them particularly well‐suited for optoelectronic hybrid dual‐channel communication. This work presents a programmable non‐volatile bipolar semi‐floating gate photovoltaic photodetector (SFG‐PD) constructed using tungsten diselenide (WSe2), hexagonal boron nitride (h‐BN), and graphene (Gra). By controlling the voltage pulses applied to the control gate, the device generates opposing built‐in electric field junctions (p+‐p and n‐p junctions), enabling reversible switching between positive and negative light responses with a rapid response time of up to 2.02 µs. Moreover, the application of this device is demonstrated in dual‐channel optoelectronic hybrid communication, offering a practical solution for achieving high‐speed, large‐capacity, low‐loss, and secure multi‐channel communication.